ANALISIS KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI TIPE KEPRIBADIAN PADA MATERI SOAL CERITA ALJABAR DI KELAS VII SMP N 1 SOKO KABUPATEN TUBAN TAHUN PELAJARAN 2022/2023 - Umah, Nur Khovifah Rohmatul; Noerruddin, Ali; Kholidah, Neneng Rika Jazilatul (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2023)
This study aims to analyze students' abilities in solving problems with Algebra word problems in terms of the personality types of class VII students at SMPN 1 Soko, Tuban Regency. This research method is a qualitative descriptive research. The subjects of this study were students in class VII F of SMPN 1 Soko, Tuban Regency in the odd semester of the 2022/2023 school year, with a total of 32 students of which 4 students were the sample. The data in this study were in the form of observations (observations), distribution of questionnaires, questions or tests of problem solving skills, and interviews with students. As for the results of the research on problem solving ability analysis in terms of personality types (Sanguinetic, Melancholic, Choleric, and Phlegmatic) in the algebra story material in class VII SMPN 1 Soko, Tuban Regency, namely from the 4 personality types, it can be seen that the melancholic personality type is a personality type that is able to through all the problem solving indicators given, the Sanguine type tends to be able to solve problems at the beginning but is unable to solve them properly and correctly, the phlegmatic type tends to be unable to understand the order of questions or problems so they cannot solve them correctly, the choleric type tends to be able to organize steps in problem solving but not fully solving and answering correctly. Keywords— Problem Solving Ability, Littauer Personality Type